2014
DOI: 10.1177/0961000613518571
|View full text |Cite
|
Sign up to set email alerts
|

Library managers’ research concerns and research competencies in Iranian special libraries

Abstract: The purpose of this study was to investigate some of the concerns of Iranian special library managers regarding research and research competencies required by special librarians. In order to achieve the objectives of this study, 21 semi-structured interviews were conducted with Iranian special library managers. The results indicated that among the participants there was generally a positive view about research. However, some obstacles were encountered, such as lack of support from the administrators of the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Only a few librarians become involved in research because of individual interests. In addition, several studies have reported that librarians face certain barriers in conducting research such as a lack of research competence (Peyvand Robati & Tahavori, 2014). Unlike organizational support, research competence and skills can be strengthened through training.…”
Section: Discussionmentioning
confidence: 98%
“…Only a few librarians become involved in research because of individual interests. In addition, several studies have reported that librarians face certain barriers in conducting research such as a lack of research competence (Peyvand Robati & Tahavori, 2014). Unlike organizational support, research competence and skills can be strengthened through training.…”
Section: Discussionmentioning
confidence: 98%
“…Studies conducted within developing countries indicated less involvement of academic librarians in research activities and mostly discussed the barriers in doing so. For instance, Peyvand Robati and Tahavori (2014) disclosed that generally the Iranian librarians had positive views about research yet they faced a number of challenges, such as lack of research competencies, less support from the administration, and lack of funding. In a recent study of Nigerian librarians, Omotunde and Alegbeleye (2021) highlighted the research productivity and work performance of academic librarians in Nigeria remained at lower level than those of in the developed countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the dawn of the twenty-first century, the pivotal role of academic libraries has been changing continuously due to the research enriched environment of higher education institutes (Peyvand Robati and Tahavori, 2014). Kennedy and Brancolini (2012) claimed that faculty, students, and staff’s demands related to research services have been increasing continuously in higher education institutions.…”
Section: Introductionmentioning
confidence: 99%
“…These competencies have been investigated from different perspectives including technological (Heim, 1986); acquisition (Fisher, 2001); chat reference (Luo, 2007); digital age (Conklin, 2017;Connor, 2018;Johnson et al, 2007;Konieczny, 2017;Saulean, 2018;Shahbazi and Hedayati, 2016;Wilkinson, 2017); data librarian (Semeler et al, 2017); research (Sorensen and DeLong, 2016); interactive relations expert (Huvila et al, 2013); and general competencies of a modern librarian (Santos, 2017). The competencies requirements have also been identified from the perspective of special libraries (Ojala, 1993;Peyvand Robati and Tahavori, 2014;Rehman and Majid, 1997).…”
Section: Introductionmentioning
confidence: 99%